Chondrichthyes Multidisciplinary Approach - Fernando da Silva Rodrigues Filho, Luis; Bráullio de Luna Sales, João (IntechOpen, 2017)
Chondrichthyes are a group of cartilaginous fish, where we have sharks, rays, and chimeras as members. This group plays an important role in aquatic ecology, as they act as predators throughout the food chain (e.g., sharks). However, many populations of Chondrichthyes are threatened by several factors (increased direct fishing, high mortality rate as accompanying fauna, marine pollution, habitat destruction, etc.). These declines are evident in many parts of the world and have come to the attention of scientists, conservation organizations, the media, and the general public. Fisheries legislation regulating international fisheries markets has been amended to provide greater protection for this group along with other species of fish. However, little is known about these species, which reinforces the importance of studies in order to have a better understanding of the elasmobranch stocks, as well as to identify the influences of the anthropic action of fishing. In response to knowledge on the low sustainability of cartilaginous fish fisheries on a global scale, FAO has developed an international plan of action for the management and conservation of these fish, with the aim of developing and implementing national plans of action to ensure management and conservation of these stocks, having as main recommendation the collection of information about the Chondrichthyes, especially the sharks. Even so, this group is little known in terms of biodiversity, ecology, behavior, and a host of other characteristics relevant to this taxon, which is very worrying. Chondrichthyes - Multidisciplinary Approach attempts to portray to the readers up-to-date information on Chondrichthyes to promote an overview of the current taxon, serving as an indispensable source of access to more accurate and detailed information on shark rays and chimeras.